2012
DOI: 10.1186/1471-2334-12-353
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal evaluation of Treponema pallidumPCR testing in early syphilis

Abstract: BackgroundSyphilis is a growing public health problem among men who have sex with men (MSM) globally. Rapid and accurate detection of syphilis is vital to ensure patients and their contacts receive timely treatment and reduce ongoing transmission.MethodsWe evaluated a PCR assay for the diagnosis of Treponema pallidum using swabs of suspected early syphilis lesions in longitudinally assessed MSM.ResultsWe tested 260 MSM for T pallidum by PCR on 288 occasions: 77 (26.7%) had early syphilis that was serologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 16 publications
0
40
0
4
Order By: Relevance
“…Gayet‐Ageron et al . reported a Tp PCR sensitivity of 75.9% for secondary syphilis, and other studies reported a sensitivity as low as 43–50% in secondary syphilis . These contradictory results could be related to different methodology used as PCR test target sequence or reference test.…”
Section: Resultsmentioning
confidence: 99%
“…Gayet‐Ageron et al . reported a Tp PCR sensitivity of 75.9% for secondary syphilis, and other studies reported a sensitivity as low as 43–50% in secondary syphilis . These contradictory results could be related to different methodology used as PCR test target sequence or reference test.…”
Section: Resultsmentioning
confidence: 99%
“…Materiałem do badań mogą być tkanki, płyn mó-zgowordzeniowy (PMR), krew (metoda o niskiej czułości) itp. [14][15][16][17][18][19][20]. Nie istnieje na świecie jedna platforma PCR zaakceptowana do diagnostyki kiły, dlatego należy używać tylko metod poddanych dokładnej walidacji i z zastosowaniem odpowiedniej kontroli jakości.…”
Section: Diagnostyka Laboratoryjnaunclassified
“…All requests for T. pallidum PCR analysis in Sydney are sent to a single laboratory. (21). All samples testing positive by PCR for the tpp47 target during this period were stored at Ϫ20°C until required.…”
Section: Methodsmentioning
confidence: 99%